NEW EMULSIFIER BASED ON WASTE OIL FROM FRYING FISH FOR LUBRICATING FUR - S.T. Sultonov; Suyunov Bunyood Gofurjonovich (Western European Studies, 2024)
This article explores the extraction and characterization of an emulsifier derived from waste oil generated during the process of frying fish, with a specific focus on its application for greasing Karakol fur. The emulsifier's chemical composition was analyzed through IR-spectroscopic analysis, and its main physical properties were thoroughly investigated. The findings revealed the presence of lubricants, esters, antibiotics, homogenous substances, and sulpho groups within the emulsifier. Moreover, the study demonstrates the economic and ecological efficacy of the newly developed emulsifier. This innovative approach not only addresses the utilization of waste oil but also presents a sustainable solution for greasing applications, emphasizing its potential as an environmentally friendly alternative
Keywords: black fur; lubricants; emulsion lubrication; emulsifier